Guidelines for Adoption Micro-frontend Architecture - Amorim, Giovanni; Rocha, Larissa; Mendes, Fabiana Freitas; Santos, Rodrigo Pereira dos; Canedo, Edna Dias (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2025)
Context: The rapid evolution of software development has led to challenges when integrating new technologies into monolithic frontend architectures. While microservices advanced backend modularity, frontends often face issues like code redundancy, scalability, and lack of modularity. The micro-frontend architecture emerged as a modular approach to address these challenges. Problem: Current monolithic frontend structures hinder agility and scalability in corporate environments, affecting both technology performance and business adaptability. This study targets challenges such as redundancy and the complexities of team coordination when scaling frontend projects. Proposed Solution: We developed a Guide for Adoption of Micro-Frontends (GAM), providing structured guidelines to support the effective implementation of micro-frontends in corporate contexts. IS Theory: This research draws upon the Technology Acceptance Model (TAM), evaluating the factors influencing the adoption of micro-frontend architecture within development teams. Method: We conducted a systematic mapping study (SMS) to investigate the impacts and challenges associated with adopting micro-frontends in software development. Next, we proposed the GAM and carried out a case study at Serasa Experian to assess the feasibility of the proposed guide. Additionally, we conducted a survey with development practitioners to explore their perceptions of the micro-frontend architecture and the workflows suggested by the GAM. Results: Results indicate that GAM is viewed positively by practitioners, assisting in the structured adoption of micro-frontends. Our case study highlights critical areas impacted by this approach, including performance, scalability, and parallel development, as well as issues with module complexity and developer experience. Contributions and Impact on IS: This research contributes a practical framework for the industry, addressing current gaps in micro-frontend implementation and setting a basis for further study on modular frontend architectures in Information Systems (IS). GAM provides actionable insights for practitioners, enhancing frontend modernization efforts with measurable impacts in agility and maintenance.